Pengaruh Komunikasi, Pelatihan Dan Kompetensi Terhadap Kinerja Karyawan Pada PT. Matahari Departemen Store Thamrin Plaza Medan - Iman Enuar Halawa; Marni Irawaty Manalu; Siti Syfa Meutia; Maya Agustina Tanjung (Maneggio: Jurnal Ilmiah Magister Manajemen, 2021)
PT.  Matahari  Department  Store  is  a  company  engaged  in   retail. This study aims to determine and analyze the effect of    communication,    training,    and    competence    on    employee performance. The research method uses quantitative. And the sampling technique used is random sampling. Based on the results,     it     is     stated     that     communication,     training,     and competence simultaneously or partially have a positive and significant influence on employee performance. Where the value   of   Ajusted   R   Square   is   0.693,   this   means   that   69.3% of the variation in employee performance variables can be explained     by     variations     in     the     communication,     training, competence variables while  the  remaining  30.7%  is  influenced  by other variables that cannot be explained in this study